International Trade, Comparative Advantage and the Incidence of Layoff Unemployment Spells - Hungerford, Thomas L. (The Review of Economics and Statistics, 1995)
The gains and losses to factors of production from trade are discussed primarily within the context of the Stolper-Samuelson theorem which focuses on factor rewards. But policy makers are more concerned about employment effects of trade. This paper focuses on the short-run effects of trade on the incidence of layoffs in U.S. manufacturing industries. A probit model with endogenous switching is employed to estimate the effects of trade shocks and explore the role of comparative advantage on layoffs. The evidence suggests that trade shocks play a minor role in the incidence of layoff spells. However, net importing industries tend to adjust their labor force through layoffs to a greater extent than net exporting industries. Copyright 1995 by MIT Press.